Can Image-Defined Risk Factors Predict Surgical Complications in Localized Neuroblastoma? - Yoneda, Akihiro; Nishikawa, Masanori; Uehara, Shuichiro; Oue, Takaharu; Usui, Noriaki; Inoue, Masami; Fukuzawa, Masahiro; Okuyama, Hiroomi (European Journal of Pediatric Surgery, 2016)
Introduction Image-defined risk factors (IDRFs) have been propounded for predicting the surgical risks associated with localized neuroblastoma (NB) since 2009. In 2011, a new guideline (NG) for assessing IDRFs was published. According to the NG, the situation in which “the tumor is only in contact with renal vessels,” should be considered to be “IDRF-present.” Previously, this situation was diagnosed as “IDRF absent.” In this study, we evaluated the IDRFs in localized NB patients to clarify the predictive capability of IDRFs for surgical complications, as well as the usefulness of the NG.Materials and Methods A total of 107 localized patients with NB were included in this study. The enhanced computed tomography and magnetic resonance images from the time of their diagnoses were evaluated by a single radiologist. We also analyzed the association of clinical factors, including the IDRFs (before and after applying the NG), with surgical complications.Results Of the 107 patients, 33 and 74 patients were diagnosed as IDRF-present (OP group), and IDRF-absent (ON group) before the NG, respectively. According to the NG, there were 76 and 31 patients who were classified as IDRF-present (NP group) and IDRF absent (NN group), respectively. Thus, 43 (40%) patients in the ON group were reassigned to the NP group after the NG. Surgical complications were observed in 17 of 82 patients who underwent surgical resection. Of the patients who underwent secondary operations, surgical complication rates were 55% in the OP group and 44% in the NP group. According to a univariate analysis, non-INSS 1, IDRFs before and after the NG and secondary operations were significantly associated with surgical complications. In a multivariate analysis, non-INSS 1 status and IDRFs after the NG were significantly associated with surgical complications.
Keywords: neuroblastoma; image-defined risk factor; surgical complication; new guideline